2002
DOI: 10.1128/mcb.22.1.171-181.2002
|View full text |Cite
|
Sign up to set email alerts
|

Absence of the CAAX Endoprotease Rce1: Effects on Cell Growth and Transformation

Abstract: After isoprenylation, the Ras proteins and other CAAX proteins undergo two additional enzymatic modifications-endoproteolytic release of the last three amino acids of the protein by the protease Rce1 and methylation of the carboxyl-terminal isoprenylcysteine by the methyltransferase Icmt. This postisoprenylation processing is thought to be important for the association of Ras proteins with membranes. Blocking postisoprenylation processing, by inhibiting Rce1, has been suggested as a potential approach for reta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
118
0
7

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 137 publications
(131 citation statements)
references
References 38 publications
(49 reference statements)
6
118
0
7
Order By: Relevance
“…To address the importance of postprenylation processing, we examined the properties of specific CAAX proteins in Rce1 Ϫ/Ϫ and Icmt Ϫ/Ϫ MEFs. We have previously found that K-Ras was mislocalized to the cytosol in both Rce1- (Kim et al, 1999;Bergo et al, 2002) and Icmtdeficient (Bergo et al, 2000) cells. In the case of the Rce1-deficient cells, the mislocalization of K-Ras was associated with reduced susceptibility to K-Ras-induced oncogenic transformation (Bergo et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…To address the importance of postprenylation processing, we examined the properties of specific CAAX proteins in Rce1 Ϫ/Ϫ and Icmt Ϫ/Ϫ MEFs. We have previously found that K-Ras was mislocalized to the cytosol in both Rce1- (Kim et al, 1999;Bergo et al, 2002) and Icmtdeficient (Bergo et al, 2000) cells. In the case of the Rce1-deficient cells, the mislocalization of K-Ras was associated with reduced susceptibility to K-Ras-induced oncogenic transformation (Bergo et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of mouse fibroblasts with either null or conditional Rce1 mutant alleles have provided compelling evidence that the membrane association, plasma membrane targeting and transformation capacity of Ras are all substantially lower when Rce1p function is lacking; in fact cells lacking Rce1 function are sensitized to FTI treatment [34][35][36] . These findings have spurred renewed interest in developing Rce1 inhibitors.…”
Section: Enzymatic Processing Of Prenylated Proteinsmentioning
confidence: 99%
“…In mammalian cells, Rce1 deficiency eliminated the endoproteolytic processing of the Ras proteins and led to a partial mislocalization of Ras proteins away from the plasma membrane (6,17). However, Rce1 deficiency had only a marginal effect on fibroblast cell growth (17).…”
mentioning
confidence: 99%
“…In yeast, RCE1 deficiency caused a partial mislocalization of Ras2p away from the plasma membrane, but there was no detectable effect on cell growth or vitality (5). In mammalian cells, Rce1 deficiency eliminated the endoproteolytic processing of the Ras proteins and led to a partial mislocalization of Ras proteins away from the plasma membrane (6,17). However, Rce1 deficiency had only a marginal effect on fibroblast cell growth (17).…”
mentioning
confidence: 99%
See 1 more Smart Citation